Cross-sectional study of the influence of gestational hyperglycemia associated with urinary incontinence on quality of life - Santini, Ana Carolina Monteiro [UNESP]; Barbosa, Angélica Mércia Pascon [UNESP]; Souza, Vanessa de Oliveira [UNESP]; Assis, Liamara Cavalcante de [UNESP]; Vianna, Luana Schineider [UNESP]; Calderon, Iracema Mattos Paranhos [UNESP]; Dias, Adriano [UNESP] (OMICS International, 2015)
During pregnancy, the prevalence of Urinary Incontinence (UI) is higher adversely impacting quality of life. Both Gestational Diabetes (GDM) and mild hyperglycemia have been associated with increased risk of UI. However, UI influence on quality of life is still poorly understood. The objective of this study was to assess the impact of UI on the quality of life of women with GDM. Method: Cross-sectional study including pregnant women allocated into 2 groups: Normoglycemic (NG) or Hyperglycemic/GDM (HG). All women classified as incontinent were asked to respond to the King’s Health Questionnaire (KHQ). Results: Of the 102 pregnant women enrolled, 69 were NG (67.6%) and 33 were HG (32.4%). UI prevalence was 55.9%. HG scores were lower for all KHQ domains with significant differences between groups regarding the scores for KHQ domains general health perception, UI impact, personal relationships emotions, and sleep/energy (p<0.05). Conclusions: UI impact was higher on pregnant women with hyperglycemia and GDM.
Keywords: Gestational diabetes mellitus; Urinary incontinence; Quality of life